2018
DOI: 10.1016/j.physa.2017.12.131
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the urban street network of Korea: Connections between topology and meta-information

Abstract: Cities consist of infrastructure that enables transportation, which can be considered as topology in abstract terms. Once cities are physically organized in terms of infrastructure, people interact with each other to form the values, which can be regarded as the meta-information of the cities. The topology and meta-information coevolve together as the cities are developed. In this study, we investigate the relationship between the topology and meta-information for a street network, which has aspects of both a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
3
11
0
1
Order By: Relevance
“…The different patterns of their SNs fundamentally depend on the scope of city planning and decision-making, geographical location, climate, economic growth, and technological adoption. Some cities have irregular (organic) street patterns with zigzag streets while others have a hierarchical (gridiron) structure with regular, rectilinear, curvilinear, orthogonal, and tree-like patterns [22]. Topographically, the majority of the cities in the ASCN, such as Bangkok [23], Manila City [24], and Ho Chi Minh City [25], are located on flatlands close to rivers or sea coasts which are vulnerable to monsoon flooding and storms [26].…”
Section: Street Network Of the Ascnmentioning
confidence: 99%
“…The different patterns of their SNs fundamentally depend on the scope of city planning and decision-making, geographical location, climate, economic growth, and technological adoption. Some cities have irregular (organic) street patterns with zigzag streets while others have a hierarchical (gridiron) structure with regular, rectilinear, curvilinear, orthogonal, and tree-like patterns [22]. Topographically, the majority of the cities in the ASCN, such as Bangkok [23], Manila City [24], and Ho Chi Minh City [25], are located on flatlands close to rivers or sea coasts which are vulnerable to monsoon flooding and storms [26].…”
Section: Street Network Of the Ascnmentioning
confidence: 99%
“…La intermediación nos muestra nodos estratégicos que controlan la estructura de toda la red de caminos y que son fundamentales para su conectividad tanto a nivel global como local. Por otra parte, precisamente esta cualidad de nodos intermediarios los convierte también en nodos en riesgo de congestión (Lee & Jung, 2018), ya que soportarán los mayores flujos de movilidad de la zona. Este aspecto es importante a la hora de informar, por ejemplo, intervenciones de rediseño y adecuación de caminos y cruces, en especial si hablamos de zonas agrarias próximas a áreas urbanas en las que pueden concurrir diferentes flujos de maquinaria agrícola pesada, vehículos a motor, bicicletas, peatones, etc.…”
Section: Discusión Y Posibles Aplicacionesunclassified
“…Along similar lines, Lee and Jung analyzed the topological features of street networks using multi-centralities methods and classified a series of cities into several groups that share common meta-information based on centrality. Their results indicated that the topological factors of the street structures are closely related to analyzing the meta-information of the city [38].…”
Section: Understanding the Relationship Between Street Network And Ementioning
confidence: 99%
“…To classify the cities by street network structure characteristics, we adopted the Gini coefficient to indicate the feature of the network structure. The Gini coefficient is widely used in economics to measure the inequality of economic quantities such as income [38,46]. It is defined as…”
Section: Hierarchical Clustering Analysismentioning
confidence: 99%